PENTINGNYA MELAKUKAN PEMANASAN DAN PENDINGINAN PADA SAAT MELAKUKAN AKTIVITAS OLAHRAGA PADA SISWA PONDOK IMBS PEKAJANGAN PEKALONGAN - Marshanda Salsabila Salsabila (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2023)
The Importance Of Warning Down When Carrying Out Sports Activities For Student At The Pekajangan Pekalongan Islamic Boarding School. One of the community service activities is socialization. Providing education on the importance of heating and cooling before and after carrying out sports activities for IMBS Pekajangan Pekalongan Islamic Boarding School students. The students of the IMBS Pekajangan Pekalongan Islamic boarding school were very enthusiastic, this activity was held before the 1st semester long holiday, with high support from the IMBS Islamic boarding school, 6 of us students with provisions from the campus, thank God, socialized it smoothly and with joy. The socialization of physical fitness education was carried out on Friday 30 December 2022 at 13.00, the place in the IMBS Pekajangan Pekalongan hall. In the student team, which consists of 6 people, each of them has their own duties, including as a presenter about the order of providing heating and cooling, there is a section that organizes student lines and there is also a photo documenter. In this activity students see and practice carefully how the presenter gives educational material the importance of warming up and cooling down before and after doing sports activities. From this we can conclude that there is very good and conducive communication from the presenters and students which students can understand. Keywords: Heating, cooling, physical fitness.